THE PROBLEM OF HISTORY OF PROGRESS OF TEST CULTURE IN UKRAINE. - S.O. Shuliak (Kherson State University, 2010)
The article is devoted to the origin of test methods and their extension at the domestic space. It is determined that Ukraine is experiencing a new stage of development testology and test culture.